Profile of Dermatophytosis among Armed Forces Personnel Attending in Combined Military Hospital, Dhaka (Journal of Armed Forces Medical College, Bangladesh, 2023)
Introduction: Dermatophytes are by far the most significant fungi because of their widespread involvement of population at large and their prevalence all over the world. They are assuming greater significance both in developed and developing countries. Hot and humid climate in the tropical and subtropical countries like Bangladesh makes dermatophytosis a very common superficial fungal skin infection. Objectives: To identify the pattern as well as the aetiological agents of dermatophytosis. Methods: It was a cross sectional study conducted at Dermatology department of CMH, Dhaka. A total 100 patients were recruited through systematic random sampling and examined for cutaneous changes. Skin, nail and hair specimens were taken from the patients and processed by potassium hydroxide preparation (KOH) for direct microscopy and culture.Results: Dermatophytosis was more common in the age group of 21-30 years (28%) and in males (64%). Most of the patients belonged to low socio-economic status (85%). Fungi was demonstrated in 74 cases (74%) either by KOH and/or culture. Dermatophytosis was more common in military persons (39%). Most common clinical type was tinea corporis (45%) followed by tinea cruris (19%). Most common aetiological agent was T. rubrum (62.7%) followed by T. mentagrophyte  (25.42%), M. gypseum (5.08%), T. tonsurans (5.08%) and E. floccosum (1.69%).Conclusion: Oral Acyclovir therapy begun within 24 hours of onset of symptoms has been shown to reduce the duration of lesions, pyrexia and overall disease duration. So, Acyclovir should be considered for persons at increased risk of severe Varicella infections.JAFMC Bangladesh. Vol 18, No 2 (December) 2022: 15-18